Optimize The Production Of Charcoal From Local Bio-Material - Umi Najwa, Maulad Mohd Noor (2012)
Charcoal is the dark grey residue produced by slow pyrolysis consists of carbon and ash. It is usually used for art, medicine, filter and fuel. The charcoal can be produced from any agricultural waste like wood, coconut shells and others. Coconut charcoal, however, is widely used for the high quality activated carbon. This research aims to optimize the production of charcoal by carbonization process. The objectives of this research are to find the optimum condition in producing the coconut based charcoal and to analyze the weight loss and the functional group of the charcoal. The production of charcoal was carried out at different carbonization temperature and different time range. The product was analyzed using FTIR. The results shown that the weight of the product decreased with increase in time and temperature. It was found that the optimum condition for producing charcoal is 450oC and 10 min. It was also found that the functional groups appeared are alkanes, alkenes and alkynes based on FTIR analysis.